The crucial role of market intelligence in the development of small business marketing capabilities. Issue 5 (19th June 2020) - Carson, Grace; O'Connor, Christina; Simmons, Geoff
Abstract : Purpose: Drawing on the resource-based view of the firm, this article explores the influences of market intelligence on the development of small business marketing capabilities, with reference to specialized marketing capabilities, architectural marketing capabilities and dynamic capabilities. Design/methodology/approach: The conceptual framework and propositions present and interpret the resource–capability complementarity between market intelligence and small business marketing capabilities and outline the relationship between individual capability sets. Findings: Market intelligence is shown to be crucial in the development of small business marketing capabilities and in the implementation of more formalized marketing strategies that allow small businesses to create value for customers and improve their performance. However, the level to which market intelligence is utilized and marketing capabilities are developed is found to be considerably influenced by the small business owner-manager and firm learning. Practical implications: It is imperative that small businesses acknowledge the practical benefits of market intelligence and harness these advantages accordingly. However, owner-managers must be motivated to encourage the development of more formalized marketing capabilities and act incisively upon the information derived from market intelligence. Originality/value: Recent research indicates that market intelligence and marketing capabilities can interact to enable a firm to align its resources with the market, by providing customer insights that guide them as to which value-adding activities they should implement. However, extant research in this area remains in its infancy, and very little is known about the adoption processes of market intelligence in small businesses and its role in developing marketing capabilities.